Ciąża w opiniach mieszkańców Rzeczypospolitej Obojga Narodów w XVIII wieku - Janicka, Jowita (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The article raises the issue of pregnancy as a special state not only in woman’s life, but also in life of people closest to her. Several opinions and advices regarding the “blessed state” (Polish expression for “a delicate state”) as seen by the population of Polish-Lithuanian Commonwealth in 18th century were quoted and discussed
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne